Adopsi Metode Scrum Untuk Elisitasi Kebutuhan Smart Tourism - Dian Niswati; Asmawati S; Nuralamsah Zulkarnaim (J-ICON : Jurnal Komputer dan Informatika, 2022)
The first step in software engineering is to get information about the scope and requirements of the system to be built. However, there are several problems that can hinder the process of designing the elicitation of smart tourism needs, such as a misunderstanding in the definition of system requirements that have been determined by one party, resulting in great potential for change. The purpose of designing the elicitation of smart tourism needs is to minimize the occurrence of change. The design of elicitation of smart tourism needs uses the scrum method which emphasizes team collaboration and is adaptive. The type of research used in this research is descriptive research with a qualitative approach. The results of the elicitation of smart tourism needs are a feature for designing smart tourism with a system design that focuses on use case diagrams using Unified Modeling Language (UML).